faktor-faktor yang mempengaruhi kepatuhan wajib pajak UMKM (Studi Kasus UMKM di Kabupaten Demak - milleniasofianti; djoko wahyudi (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2022)
Taxes are very important because taxes make a large contribution to state revenue.This study aims to analyze the effect of tax knowledge, taxpayer awareness, tax sanctions, tax service services on taxpayer compliance. The population used in this study is the Taxpayer of Micro, Small and Medium Enterprises in Demak Regency. Sampling in this study was carried out by purposive sampling or samples were selected based on certain criteria. The sample that will be taken in this study is as many as 110 taxpayers in Demak Regency. Descriptive statistical tests and multiple regression tests with SPSS 22 were used to analyze the data. This study shows that the independent variable knowledge of taxation and service tax authorities have a significant positive effect on taxpayer compliance, taxpayer awareness and tax sanctions have no effect on taxpayer compliance.